Penguatan Penegakan Etika Pariwara Indonesia dalam Iklan Luar Griya, Studi dalam Iklan Pemilihan Walikota dan Wakil Walikota Yogyakarta - Rohmad, Muhammad Furqon Dwi Nur; Al-Azhar, Muhammad Fachrul Ikhsan; Fadli, Hanip; Muktaf, Zein Mufarrih (Universitas Muhammdiyah Yogyakarta, 2025)
This study aims to analyze violations of the Indonesian Advertising Ethics (EPI) in the billboard advertisements of the Yogyakarta mayoral and deputy mayoral candidates, Heroe Pena, during the 2024 election campaign. The advertisements use superlative terms such as